Aftershock seismicity and tectonic setting of the 2015 September 16 Mw 8.3 Illapel earthquake, Central Chile. Issue 2 (8th June 2016) - Lange, Dietrich; Geersen, Jacob; Barrientos, Sergio; Moreno, Marcos; Grevemeyer, Ingo; Contreras-Reyes, Eduardo; Kopp, Heidrun
Abstract: Powerful subduction zone earthquakes rupture thousands of square kilometres along continental margins but at certain locations earthquake rupture terminates. To date, detailed knowledge of the parameters that govern seismic rupture and aftershocks is still incomplete. On 2015 September 16, the M w 8.3 Illapel earthquake ruptured a 200 km long stretch of the Central Chilean subduction zone, triggering a tsunami and causing significant damage. Here, we analyse the temporal and spatial pattern of the coseismic rupture and aftershocks in relation to the tectonic setting in the earthquake area. Aftershocks cluster around the area of maximum coseismic slip, in particular in lateral and downdip direction. During the first 24 hr after the main shock, aftershocks migrated in both lateral directions with velocities of approximately 2.5 and 5 km hr −1 . At the southern rupture boundary, aftershocks cluster around individual subducted seamounts that are related to the downthrusting Juan Fernández Ridge. In the northern part of the rupture area, aftershocks separate into an upper cluster (above 25 km depth) and a lower cluster (below 35 km depth). This dual seismic–aseismic transition in downdip direction is also observed in the interseismic period suggesting that it may represent a persistent feature for the Central Chilean subduction zone.